Optimism in Migrant Workers in Asia: Systematic Literature Review - Siti Muslimah; Unika Prihatsanti (International Journal Labs, 2022)
This literature review aims to examine the literature on the optimistic attitude of Asian migrant workers. As databases, Science Direct, Springer Link, Emerald Insight, and JSTOR were used. Based on the inclusion and exclusion, there are three criteria for journal articles. The study results show that migrant workers were optimistic and had a strong spirit because of the social support and the fulfilment of health services in their workplace. However, they experience lousy behavior from local domestic workers as jobs clarity by migrant workers resulting in unemployment and labor market competition.